Speech activity detection using accelerometer - Matic, A.; Osmani, V.; Mayora, O. (2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2012)
The level of social activity is linked to the overall wellbeing and to various disorders, including stress. In this regard, a myriad of automatic solutions for monitoring social interactions have been proposed, usually including audio data analysis. Such approaches often face legal and ethical issues and they may also raise privacy concerns in monitored subjects thus affecting their natural behaviour. In this paper we present an accelerometer-based speech detection which does not require capturing sensitive data while being an easily applicable and a cost-effective solution.